VOZES DA PEDAGOGIA: DESMISTIFICANDO A LICENCIATURA - Silva Pereira, Aline Conceição; Rodrigues Ferreira, Cristiane; Aparecida Muniz, Daise; Santos Batista Bispo, Juliana; Cristina Franco de Lima, Lárien; Gomez Franco, Lorenna; Sanches Tizzo, Vinícius (Intercursos, 2025)
não consta